Interrelationship Between Obstructive Sleep Apnea Syndrome and Severe Asthma: From Endo-Phenotype to Clinical Aspects - Ragnoli, Beatrice; Pochetti, Patrizia; Raie, Alberto; Malerba, Mario (Frontiers in Medicine, 2021)
Sleep related breathing disorders (SBD) are characterized by abnormal respiration during sleep. Obstructive sleep apnea (OSA), a common disorder that is increasingly being recognized because of physician awareness, is characterized by recurrent episodes of partial or complete closure of the upper airway resulting in disturbed breathing during sleep. OSA syndrome is associated with decreased quality of life and significant comorbidities. Also the prevalence of asthma is rising. Many patients suffering from asthma report poor sleep, often attributed to nocturnal worsening of their asthma, increased daytime sleepiness, and a higher prevalence of snoring as compared to the general population. Such symptoms are common in OSA, suggesting an association between the two conditions. Moreover, risk factors common to both diseases include obesity, rhinitis, and gastroesophageal reflux. It was suggested a bi-directional correlation between asthma and OSA, with a mutual negative effect in term of severity: while OSA is an independent risk factor for asthma exacerbations, it can also worsen asthma and vice-versa. We investigate the interrelationship between OSA and severe asthma, from endo-phenotype to clinical aspects, discussing literature data and implications and future directions.